17th International Conference on the Physics of Highly Charged Ions (Journal of physics. Conference series, 2015)
The 17th edition of the International Conference on the Physics of Highly Charged Ions (HCI 2014) was held in San Carlos de Bariloche, in the southern region of Argentina known as Patagonia, from August 31 to September 5, 2014. This meeting corresponds to a series of HCI conferences, which has been held every other year since 1982 in cities in Europe, USA, Japan and China. This was the first time that the conference took place in Latin America. This edition was organized by a Local Committee made up of physicists mainly from the cities of Bariloche and Rosario and also from Buenos Aires and Bahía Blanca, all sites where research on Atomic Collisions is developed. The conference was attended by delegates coming from 18 countries, more that 23% of whom were women. The field of highly charged ions has seen in recent years a promising evolution originating from bold progress in theory and significant advances in experimental techniques. The HCI conferences aim at bringing together experimentalists and theoreticians from as wide a range of fields as, for instance, Fundamental Aspects, Structure and Spectroscopy, Collisions with Electrons, Ions, Atoms and Molecules, Interaction with Clusters, Surfaces and Solids, Interactions with Photons and Plasmas, Strong Field Processes, and Production, Experimental Developments and Applications. The Scientific Programme, selected by an International Advisory Board, included 5 Review Lectures, 11 Progress Reports, 1 Local Report and 24 Special Reports. In addition, the results of 132 contributed works were presented as poster communications and a Public Lecture on 'The wonders of the Southern Skies' was delivered by an Argentinean expert. Thus, a wide range of subjects comprising a balanced mix of topics was covered throughout the course of the conference. The HCI 2014 was a resounding success for the international and local communities, from both the scientific and social aspects, considering that the attendees and accompanying persons had the opportunity to enjoy a comfortable and friendly ambiance as well as the beautiful landscapes of the region including big lakes and high mountains. During the conference vivid and interesting scientific discussions were maintained by the participants in a relaxed environment. The Local Organizing Committee would like to recognize the generous contributions made by various institutions: International Pure and Applied Physics (IUPAP), Comisión Nacional de Energía Atómica (CNEA), Consejo Nacional de Investigaciones Científicas y Técnicas (CONICET), Investigación Aplicada S. E. (INVAP), Patagonia Norte Division of CONICET, Instituto Balseiro and NEC Corporation. The Local Chairs would like to express their gratitude to all the other members of the Local Organizing Committee who collaborated with a great effort and in countless ways to the success of the conference. In particular, we thank Omar Fojón for the outstanding collaboration received, and Juan Manuel Monti, who worked hard for the production of the Book of Abstracts and other related activities. We also would like to thank Renata Della Picca, Juana Gervasoni and Silvina Seguí, for their generous work in printing the book of abstracts, bags, banners, etc. and for their continuous help at the Registration Desk. We extend our gratitude to the younger members of the Local Organizing Committee, Marcos Feole, Francisco Navarrete and Juan Martín Randazzo for their help with the poster logistics; and to Luis Rodríguez for ensuring that all the presentations were ready and on schedule. We thank María Silvia Gravielle, our colleague and liaison in Buenos Aires, for helping delegates to get their visas on time; Sebastián Otranto and Jocelyn Hanssen, for their early work collecting and sorting the talk's proposals and Carlos Stia, for helping with the revision of the style of the manuscripts. We also thank M. Galassi, P Focke and D. Fregenal. We recognize Sergio Suárez, for getting funding from private sources and Roberto Garibotti, for his help with the edition of the book of abstracts. We thank Lynn van Brook for her work as conference secretary, and Silvana Peralta and Natalia Mastrángelo, for the web development and graphic design. Finally, we express our acknowledgements to the scientists that participated during the refereeing process of the present Proceedings. Raúl Barrachina Flavio Colavecchia Roberto Rivarola Local Chairs, HCI 2014 December 2014